Comparison of impression techniques and materials for an implant-supported prosthesis - Del’Acqua, Marcelo Antonialli; Chávez, Alejandro Muñoz [UNESP]; Amaral, Ângela Líbia Chagas [UNESP]; Compagnoni, Marco Antonio [UNESP]; De Assis Mollo, Francisco [UNESP] (My University, 2010)
Purpose: To investigate, in vitro, the dimensional accuracy of two impression techniques (squared impression copings and squared impression copings sandblasted and coated with impression adhesive) made of vinyl polysiloxane and polyether impression materials. Materials and Methods: A master cast (control group) with four parallel implant abutment analogs, a passive framework, and a custom aluminum tray was fabricated. Four groups (n = 5 each group) were tested: squared Impregum (SI), squared Express (SE), sandblasted adhesive squared Impregum (ASI), and sandblasted adhesive squared Express (ASE). The measurement method employed was just one titanium screw tightened to the framework. A stereomicroscope was used to evaluate the fit of the framework by measuring the size of the gap between the abutment and the framework. The results were analyzed statistically. Results: The mean values for the abutment/framework interface gaps were: master cast, 31.63 µm (SD 2.16); SI, 38.03 µm (SD 9.29); ASI, 46.80 µm (SD 8.47); SE, 151.21 µm (SD 22.79); and ASE, 136.59 µm (SD 29.80). No significant difference was detected between the SI or ASI techniques and the master cast. No significant difference was detected between the SE and ASE techniques. Conclusion: Within the limitations of this study, it can be concluded that Impregum Soft medium consistency was the best impression material and the impression technique did not influence the accuracy of the stone casts. © 2010 by Quintessence Publishing Co Inc.
Keywords: Dental implant; Implant impression technique; Impression material